2022
DOI: 10.32604/cmc.2022.020823
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cryptocurrency Prediction Method Using Optimum CNN

Abstract: In recent years, cryptocurrency has become gradually more significant in economic regions worldwide. In cryptocurrencies, records are stored using a cryptographic algorithm. The main aim of this research was to develop an optimal solution for predicting the price of cryptocurrencies based on user opinions from social media. Twitter is used as a marketing tool for cryptoanalysis owing to the unrestricted conversations on cryptocurrencies that take place on social media channels. Therefore, this work focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Its purpose is to extract unique characteristics from grouped on-chain inputs. Hasan et al [9] suggested an approach that was optimized by employing CNN, and by modifying the parameters, they were able to produce extremely accurate results. When it comes to the prediction of time-series data, neural networks provide superior performance compared to the most advanced machine learning algorithms.…”
Section: B Related Workmentioning
confidence: 99%
“…Its purpose is to extract unique characteristics from grouped on-chain inputs. Hasan et al [9] suggested an approach that was optimized by employing CNN, and by modifying the parameters, they were able to produce extremely accurate results. When it comes to the prediction of time-series data, neural networks provide superior performance compared to the most advanced machine learning algorithms.…”
Section: B Related Workmentioning
confidence: 99%
“…Fig. 4 The hidden layer LSTM memory cell structure [24] D. Convolutional Neural Networks It is well known that this model has been used to recognize patterns and features in photos, videos, and audio signals and that it did so with surprisingly excellent results [28]. In this study, 1D CNN models presented in Fig 5, where the data and kernels are one-dimensional vectors, were taken into consideration.…”
Section: Long Short-term Memory (Lstm)mentioning
confidence: 99%
“…5 Basic Convolutional Neural Networks Architecture [15] In order to learn hierarchical representations of the input data, CNNs make use of a number of essential components [27]. Beginning with one or more convolutional layers, CNNs conduct convolution to extract local features by sliding filters or kernels over the input data [28]. After each convolutional layer, activation functions, often ReLUs (Rectified Linear Units), induce nonlinearity.…”
Section: Long Short-term Memory (Lstm)mentioning
confidence: 99%
“…Although individuals often Tweet favorably about cryptocurrencies as their values fall, Twitter attitude research believes forthcoming price levels will become favorable. As a result of their volatile nature in the current market, predicting cryptocurrency values is a difficult endeavor [31].…”
Section: Digital Promotion and Cryptocurrency Data Analysismentioning
confidence: 99%